Dose mapping in Cesium-137 blood irradiator using novel Ge-doped silica optical fibres in comparison with gafchromic EBT-XD film: A preliminary study - Bakar, K.S.A.K.; Noor, N. M.; Hassan, Faridah Haji; Idris, F.; Bradley, D.A. * (Elsevier, 2023)
The purpose of dose-mapping in blood irradiation is to ensure radiation dose delivered to the blood bags is within the specified limits of minimum 15 Gy and maximum 50 Gy, thus preventing any blood transfusion-related diseases. In the present study, we investigated the feasibility of novel fabricated germanium-doped (Ge-doped) silica-based optical fibre as a potential passive dosimeter for dose-mapping of a Cesium-137 (Cs-137) gamma blood irradiator. The calibration curve of optical fibres and Gafchromic EBT-XD film was established by irradiating the samples in the dose range from 5 to 35 Gy at the central of a water-equivalent phantom in a dedicated blood irradiator machine. For dose mapping, the fabricated optical fibres and EBT-XD film were irradiated for a gamma exposure of 8 min and 56 s to deliver a central dose of 25 Gy. Thermoluminescence measurements were performed using a Harshaw 3500 TLD reader at a maximum acquisition temperature of 400 °C. The results of optical fibres were compared with EBT-XD film. The absorbed dose obtained from optical fibres shows deviation of within 0.1%–10.4% compared to that of dose of the film. The fabricated optical fibre studied in this work have a good potential as a new passive dosimeter for characterisation and dose mapping of gamma blood irradiator due to its high sensitivity and reproducible characteristics.